Posterior Tibial Slope Angle Correlates With Peak Sagittal and Frontal Plane Knee Joint Loading During Robotic Simulations of Athletic Tasks. (July 2016) - Bates, Nathaniel A.; Nesbitt, Rebecca J.; Shearn, Jason T.; Myer, Gregory D.; Hewett, Timothy E.
Background: Tibial slope angle is a nonmodifiable risk factor for anterior cruciate ligament (ACL) injury. However, the mechanical role of varying tibial slopes during athletic tasks has yet to be clinically quantified. Purpose: To examine the influence of posterior tibial slope on knee joint loading during controlled, in vitro simulation of the knee joint articulations during athletic tasks. Study Design: Descriptive laboratory study. Methods: A 6 degree of freedom robotic manipulator positionally maneuvered cadaveric knee joints from 12 unique specimens with varying tibial slopes (range, −7.7° to 7.7°) through drop vertical jump and sidestep cutting tasks that were derived from 3-dimensional in vivo motion recordings. Internal knee joint torques and forces were recorded throughout simulation and were linearly correlated with tibial slope. Results: The mean (±SD) posterior tibial slope angle was 2.2° ± 4.3° in the lateral compartment and 2.3° ± 3.3° in the medial compartment. For simulated drop vertical jumps, lateral compartment tibial slope angle expressed moderate, direct correlations with peak internally generated knee adduction ( r = 0.60-0.65), flexion ( r = 0.64-0.66), lateral ( r = 0.57-0.69), and external rotation torques ( r = 0.47-0.72) as well as inverse correlations with peak abduction ( r = −0.42 to −0.61) and internal rotation torques ( r = −0.39 to −0.79). Only frontal plane torques were correlated during sidestep cutting simulations. For simulated drop vertical jumps, medial compartment tibial slope angle expressed moderate, direct correlations with peak internally generated knee flexion torque ( r = 0.64-0.69) and lateral knee force ( r = 0.55-0.74) as well as inverse correlations with peak external torque ( r = −0.34 to −0.67) and medial knee force ( r = −0.58 to −0.59). These moderate correlations were also present during simulated sidestep cutting. Conclusion: The investigation supported the theory that increased posterior tibial slope would lead to greater magnitude knee joint moments, specifically, internally generated knee adduction and flexion torques. Clinical Relevance: The knee torques that positively correlated with increased tibial slope angle in this investigation are associated with heightened risk of ACL injury. Therefore, the present data indicated that a higher posterior tibial slope is correlated to increased knee loads that are associated with heightened risk of ACL injury.